Blockchain technology for smart city and smart tourism: latest trends and challenges. Issue 4 (3rd April 2021) - Nam, Kichan; Dutt, Christopher S.; Chathoth, Prakash; Khan, M. Sajid
ABSTRACT: Blockchain is one of the latest network-based technologies, which will have significant impact on most industries including tourism. Even though blockchain technology is at the infancy stage of development, tools such as cryptocurrencies, smart contracts, and Decentralised Applications have begun to influence tourism transactions. This paper makes an attempt to highlight the key characteristics of blockchain technology in conjunction with the smart city/tourism framework while making propositions of how the technology would evolve and influence the industry. Major issues related to the technology as well as challenges are also discussed, including some misconceptions.